2012
DOI: 10.1148/radiol.11110364
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and Prognostic Value of Modified Coronary Artery Calcium Score, FEV1, and Emphysema in Lung Cancer Screening Population: The MILD Trial

Abstract: mCAC is a better predictor of CVE and all-cause mortality than FEV1 and emphysema extent and may contribute to the identification of high-risk individuals in a lung cancer screening setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 34 publications
11
70
1
Order By: Relevance
“…Several investigators have studied the association between pulmonary function and subsequent cardiovascular disease [16][17][18]20]. Our data are consistent with these studies as we observed clear trends across quartiles of FEV 1 %predicted, similar to Schroeder et al [16], linking pulmonary function impairment with cardiovascular events.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several investigators have studied the association between pulmonary function and subsequent cardiovascular disease [16][17][18]20]. Our data are consistent with these studies as we observed clear trends across quartiles of FEV 1 %predicted, similar to Schroeder et al [16], linking pulmonary function impairment with cardiovascular events.…”
Section: Discussionsupporting
confidence: 92%
“…This association persisted after controlling for age, smoking status and packyears. Sverzellati et al investigated the association between CT quantified emphysema and the prediction of cardiovascular events [20]. Similar to our study, they found that coronary calcium was the strongest predictor for cardiovascular events, though in contrast we did observe an association between cardiovascular events and CT quantified emphysema and FEV1%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most commonly used slice thicknesses were 2.5/3 mm and 5 mm. Four studies used a (medium-) smooth kernel, 10,20,21,25 the other studies did not indicate the applied kernel. Six studies used Agatston scoring, 10,[17][18][19]21,25 whereas 4 others used visual grading of the presence and extent of coronary calcification.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…prognosis in chronic obstructive pulmonary disease (COPD) (10)(11)(12)(13)(14), among smokers (15), and in the general population (16) independent of lung function.…”
mentioning
confidence: 99%